An estimation of the correctness of XRD results obtained from the analysis of materials with bimodal crystallite size distribution. Issue 43 (8th October 2015) - Uvarov, Vladimir; Popov, Inna
Abstract : 36 powder artificial mixtures and 2 usual samples with a bimodal crystallite size distribution have been prepared and examined by an X-ray diffraction method. Rietveld refinement at a "double-phase model" mode was used for analysis. Abstract : 36 powder artificial mixtures and 2 usual samples with a bimodal crystallite size distribution have been prepared and examined by an X-ray diffraction method. We estimated the capability of the Rietveld refinement at a "double-phase model" mode and the correctness of the results. The homogeneity and the crystallite sizes of pure phases used in the preparation of the mixtures were checked by TEM. In most cases, Rietveld refinement at a "double-phase model" mode provided reliable information about both the crystallite size and percentage of constituents. Reliability of XRD results was higher for the powder mixtures with a larger difference in crystallite sizes. It was found that the shape of the crystallites can have a significant impact on the analysis results, and for columnar crystals, the employed method did not always provide correct results. When size distribution of the material deviates from a bimodal one, the correctness of the result decreases. Such an investigation was performed for the first time.